Strontium-modified premixed calcium phosphate cements for the therapy of osteoporotic bone defects. (January 2018) - Lode, A.; Heiss, C.; Knapp, G.; Thomas, J.; Nies, B.; Gelinsky, M.; Schumacher, M.
Graphical abstract: Abstract: In this study a premixed strontium-containing calcium phosphate bone cement for the application in osteoporotic bone defects has been developed and characterised regarding its material and in vitro properties as well as minimally invasive applicability in balloon kyphoplasty. Strontium was introduced into the cement by substitution of one precursor component, CaCO3, with its strontium analogue, SrCO3 . Using a biocompatible oil phase as carrier liquid, a cement paste that only set upon contact with aqueous environment was obtained. Strontium modification resulted in an increased strength of set cements and radiographic contrast; and the cements released biologically relevant doses of Sr 2+ -ions that were shown to enhance osteoprogenitor cell proliferation and osteogenic differentiation. Finally, applicability of strontium-containing cement pastes in balloon kyphoplasty was demonstrated in a human cadaver spine procedure. The cement developed in this study may therefore be well suited for minimally invasive, osteoporosis-related bone defect treatment. Statement of Significance: Strontium-releasing calcium phosphate bone cements are promising materials for the clinical regeneration of osteoporosis-related bone defects since they have been shown to stimulate bone formation and at the same time limit osteoclastic bone resorption. Today clinical practice favours minimally invasive surgical techniques, e.g. for vertebral fracture treatment, posing special demands on such cements. We have therefore developed a premixed, strontium-releasing bone cement with enhanced mechanical properties and high radiographic visibility that releases biologically relevant strontium concentrations and thus stimulates cells of the osteogenic lineage. In a pilot experiment we also exemplify its excellent suitability for minimally invasive balloon kyphoplasty procedures.